E-peroxone process of a chlorinated compound: Oxidant species, degradation pathway and phytotoxicity. Issue 4 (August 2022) - Amado-Piña, Deysi; Roa-Morales, Gabriela; Molina-Mendieta, Mayela; Balderas-Hernández, Patricia; Romero, Rubi; Barrera Díaz, Carlos E.; Natividad, Reyna
Abstract: An electro-peroxone (EP) process was conducted in an up-flow bubble column reactor with BDD electrodes. The efficiency of the process was tested in the 4-Chlorophenol (4-CPh) mineralization and compared with that attained by single treatments like ozonation (O3 ) and electro-oxidation (EO). At [TOC]o = 56 mg·L −1, pHo = 7.0, T = 293 K, j  = 0.06 A·cm −2, t  = 120 min, the oxidation power decreased in the following order EP>EO>O3, and the TOC removed was, in the same order, 100%> 93%> 40%. The calculated synergy coefficient was 0.31, while the mineralization current efficiency percentage (MCE%) and the energy consumption (EC) were 12.24% and 11.48%, 2.84 and 2.31 kW·h −1, for EP and EO, respectively. The germination percentage of Lactuca sativa, was 100%, 30% and 20%, at the end of EP, EO and O3, respectively. This indicates that phytotoxicity, was only eliminated with EP. Based on the by-products, e.g. aromatic compounds (4-chlorocatechol, catechol, phenol, p-benzoquinone, hydroquinone) and carboxylic acids (maleic, formic, fumaric, succinic, oxalic, malonic and acetic acids) identified by UHPLC-UV/DAD and the changes of the concentration of chloride ion (Cl - ), hypochlorite, chlorite, chlorate and perchlorate, a reaction pathway was proposed for the 4-CPh mineralization by the E-peroxone process. It was demonstrated that under the studied conditions both, hydrogen peroxide and ozone, are produced during EO. At the end of EO, H2 O2, carboxylic acids and perhaps persulfates, are responsible for the phytotoxicity of the solution. Graphical Abstract: ga1 Highlights: The mineralization efficiency of 4-CPh is in the order EP>EO>O3 . The removal phytotoxicity efficiency of a 4-CPh solution is in the order EP>EO>O3 . Only electroperoxone (EP) removes phytotoxicity completely. The remained toxicity after EO and O3, is due to H2 O2, carboxylic acids, sulfates and persulfates. C l −, Cl O 3 − and Cl O 4 − are produced and remain after EP and EO. In O3, only Cl O 3 − and Cl - remain.